Analisis Upaya K3 Terhadap Faktor Risiko Kebisingan Pada Bagian Weaving (Penenunan) di Industri Tekstil PT. Primissima, Sleman, Yogyakarta - Ega Dwi Ifaafah; Agus Suwarni; Mohamad Mirza Fauzie (Sanitasi: Jurnal Kesehatan Lingkungan, 2015)
Labors at weaving unit of textile industries work in an environment condition that is highly exposed directly to noise generated by the loom production machines. The purpose of this study was to know the implementation of health and safety efforts towards that noise’s risk factors at the weaving unit of PT Primissima, by conducting a research with descriptively survey approach. The study sample were obtained purposively, and by using a defined criteria of at least one year working period, 43 workers were eligible for being the respondents. Data were collected by interview and observation, and then were analyzed descriptively. The results of the study revealed that the noise intensity in the weaving unit did not comply the threshold, and the efforts that has been done consisted of: isolation at production room, provision of ear protectors devices by the company in the form of cotton and its use by the labors, periodic medical examinations were carried out once a year for those who were indicated had declining health condition, explanation ofthe job procedures at labor’s initial service, training of health and safety for labors who prospective to managerial carrier, and the provision of health insurance by participating in Jamsostek program. The efforts related with isolation, ear protectors tools, periodic medical check-up and HSE training, have not fulfilled the regulations; however, the explanation of work procedures as well as the health insurance provision, had been implemented appropriately.